General páley problem - Kondratyuk, Ya. V.; Kondratyuk, A. A.; Tarasyuk, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
In the class of functions u of finite lower order subharmonic in ℝ p+2,p ∈ ℕ we establish an exact upper bound for _r → ∞ m_q (r,u^ + ) T(r,u) , 1< q ∞ , whereT(r, u) is a Nevanlinna characteristic of the function u andm q (r, u +) is the integralq-mean of the functionu +,u + = max(u,0), on the sphere of radiusr.